A high-fat challenge increases airway inflammation and impairs bronchodilator recovery in asthma - Wood, Lisa G.; Garg, Manohar L.; Gibson, Peter G. (Journal of allergy and clinical immunology, 2011)
Dietary fat activates systemic innate immune responses, but the effect on airway responses is unknown. To examine effects of a high-fat versus low-fat meal on systemic and airway inflammation in asthma. Nonobese subjects with asthma were randomized to consume a high-fat (n = 19; 48% [49 g] fat) or low-fat (n = 18; 15% [3 g] fat) meal. Fourteen obese patients with asthma and 21 healthy controls also consumed a high-fat meal. Another group of patients with asthma consumed a high-trans (n = 5; 5.2 g trans fat) or nontrans (n = 5, <0.3 g trans fat) fatty acid meal. Lung function was measured at baseline (prebronchodilator) and 2, 3, and 4 hours after bronchodilator. Airway inflammation was assessed by using induced sputum cell counts and Toll-like receptor 4 mRNA expression by real-time PCR. Systemic inflammation was measured by ELISA quantification of plasma TNF-α, high-sensitivity C-reactive protein, and IL-6 concentrations. In patients with asthma, at 4 hours postmeal, increases in sputum % neutrophils and Toll-like receptor 4 mRNA expression were higher and increases in FEV 1/forced vital capacity (FVC) were lower in the high-fat versus low-fat groups. Changes in plasma fatty acids correlated with changes in sputum % neutrophils and were negatively associated with changes in % FEV 1, % FVC, and FEV 1/FVC. After the high-trans fatty acid meal, sputum % neutrophils were significantly higher than after the nontrans meal. A high-fat meal augments neutrophilic airway inflammation, with the effect dependent on the type of fat consumed. A high-fat meal also suppresses bronchodilator recovery in asthma. Modifying dietary fat intake may be useful in asthma.